Matercergrado: mobile application for learning mathematics in third grade of elementary school - Cesar Pescador Monroy; Yedid Erandini Niño Membrillo; Rosa María Rodríguez Aguilar (Universidad de Guadalajara, 2024)
The objective of this article was to demonstrate that the third-grade elementary school mobile application for mathematics, Matercergrado, enhanced collaborative problem-solving. The instructional design of the application followed the ADDIE methodology, and its creation employed the Mobile-D methodology. The research approach was mixed and descriptive, with a convenience sample of 18 participants from an elementary school in the municipality of Nezahualcóyotl, State of Mexico. These participants completed a Likert-type survey, validated using the Delphi method and Cronbach's Alpha, which evaluated usability, interface design, functionality, thematic content, and comprehension of exercises and components. The results indicated that students highly appreciated Matercergrado, and teachers validated its thematic content and explanatory procedures for teaching mathematics. In addition, students reported collaborative and union sentiments while solving problems and doing exercises. Overall, Matercergrado achieved excellent results during the study, showing the potential to enhance students' understanding and academic performance.